Exploring Arabic Grammar (Nahwu) Instruction through Al-Muyassar fi ‘Ilm al-Nahw: A Case Study at BAEC in an Indonesian Islamic Boarding School - Muhammad Wafiq Mudzakir; Asep Sunarko; Ngatoillah Linnaja (Edu Journal Innovation in Learning and Education, 2026)
This study aims to analyze the transformation of Arabic grammar (nahwu) learning through the use of the Nahwu Muyassar book in the Badar Arabic English Club (BAEC) program at Baitul Abidin Darussalam Islamic Boarding School, Wonosobo. This research employed a qualitative approach with a case study design. The subjects consisted of two Arabic language teachers and fifteen students participating in the BAEC program, selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings show that the use of Nahwu Muyassar facilitates students’ understanding of basic Arabic grammar rules because the material is presented in a concise, systematic, and practical manner. In addition, the integration of grammar instruction with a communicative approach through muhadatsah practice makes the learning process more contextual, interactive, and meaningful. These findings indicate that the use of simplified teaching materials combined with a communicative method can serve as an innovative alternative to improve the effectiveness of nahwu learning in Islamic boarding schools